(untitled) (KYAMC Journal, 2023)
Background: Mental disorder account for 13% global burden of disease which has affected more than 970 million people worldwide in 2017. About 1 in 17 suffers from serious mental illness in worldwide. Therefore, the affected person is dependent on caregiver and their wellbeing is directly related to nature and quality of care provided by caregiver. Caregiver are especially vulnerable as they face complex, high burden care situation resulting in higher caregiver stress. The aim of this study is to determine the level of stress and coping of caregivers of Psychiatric patients. Materials and Methods: This cross sectional study was conducted among 171 caregivers, aged more than 18 years in National Institute of Mental Health (NIMH) Shyamoli, Dhaka. Study period was from 1 January to 31 December 2020. The research participants were selected following the convenient sampling method based on defined selection criteria. A semi-structured questionnaire was developed and the respondents were interviewed face to face individually while maintaining privacy and confidentiality. Result: Distribution of the socio demographic status of the study participants were females74% and male 26%. Their mean age was 40.09(±13.31) years. In educational level 33.9 % of the participants were illiterate, secondary level education up to 21.1%. In occupation housewife 57.9%, service holder 18.7%. Caregiver having 76.6% moderate stress, low stress 21.6% and 1.8% having high perceived stress. Association between stress and coping average, good coping 74.8% and 88.2% had moderate stress respectively. Their significant P value .009(p<0,05). The person’s correlation present between stress and coping was positive. The correlation co-efficient was .06 (p<0.05). So, there was a weak positive correlation between level of stress and coping status. Conclusion: Health care personal may screen the stress level of caregivers and if there is any functional impairment is present, they could proper evaluation and therapeutic intervention. KYAMC Journal Vol. 13, No. 04, January 2023: 240-244